A Cost Analysis of Kidney Replacement Therapy Options in Palestine. (3rd March 2015) - Younis, Mustafa; Jabr, Samer; Al-Khatib, Abdallah; Forgione, Dana; Hartmann, Michael; Kisa, Adnan
This study provides a cost analysis of kidney replacement therapy options in Palestine. It informs evidence-based resource allocation decisions for government-funded kidney disease services where transplant donors are limited, and some of the common modalities, i.e., peritoneal dialysis (PD) and home hemodialysis (HD), are not widely available due to shortages of qualified staff, specialists, and centers to follow the patient cases, provide training, make home visits, or provide educational programs for patients. The average cost of kidney transplant was US$16 277 for the first year; the estimated cost of HD per patient averaged US$16 085 per year—nearly as much as a transplant. Consistent with prior literature and experience, while live, related kidney donors are scarce, we found that kidney transplant was more adequate and less expensive than HD. These results have direct resource allocation implications for government-funded kidney disease services under Palestinian Ministry of Health. Our findings strongly suggest that investing in sufficient qualified staff, equipment, and clinical infrastructure to replace HD services with transplantation whenever medically indicated and suitable kidney donors are available, as well as deploying PD programs and Home HD programs, will result in major overall cost savings. Our results provide a better understanding of the costs of kidney disease and will help to inform Ministry of Health and related policy makers as they develop short- and long-term strategies for the population, in terms of both cost savings and enhanced quality of life.